Design of a coffee brush crusher for organic compost in the jungle of the Junín region of Peru - De la Cruz Flores, Jhon Anderson (2025)
Every year, 750,000 tonnes of waste coffee brushwood are dumped in the jungle of the Junín region of Peru. The purpose of this study is to promote a circular economy and mitigate the environmental impact. This article focused on the design of a crushing machine adapted to the needs of local small farmers in the central jungle. The design process was based on the VDI 2221 (Guidelines of the German Association of Engineers 2221) methodology, focused on finding effective solutions to facilitate the generation of organic compost. Detailed calculations of the key elements of the machine were carried out, complemented with CAD (Computer Aided Design) simulations such as SolidWorks and Altair EDEM, to evaluate stress resistance and the pressure required to crush the coffee brush. In addition, field studies were conducted to gather data on the essential requirements that influenced the design. As a result, the maximum pressure of the machine was obtained, giving a value of 3139.3 N/m^2. In addition, a crushing output of 720 kg/h was achieved, improving efficiency compared to manual methods and maximizing time and resource utilization. This approach not only addresses waste, but also contributes to the sustainable development of the region. In conclusion, the machine reduces the moisture content of the coffee brush and decreases the decomposition time by 50% compared to the anaerobic process. In this way, organic compost rich in nutrients is obtained for the soil.